Presuppositions in Literary Translation: A Corpus-Based Approach - Şerban, Adriana (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis paper investigates the use of existential presuppositions in a corpus of literary translations from Romanian into English (novels and short stories). In particular, we are interested in ascertaining whether there are any differences between the ways in which definiteness and indefiniteness are used in translations compared to source texts, and whether any pattern can be found to be in operation; the aim is to explore presuppositions in terms of what they can tell us about translators’ assumptions about their readers. The main finding is the presence of a [- definite] trend in the corpus, whereby definite references tend to be translated by indefinite references. The study suggests that this is linked to distancing; i.e., target readers are presented with texts which position them as distant observers, rather than in-the-know in-group members.